Mudanças climáticas e vulnerabilidade em comunidades rurais: indicadores e índice para pequenas localidades - Gadelha, Denise Pinto (2020)
The main objective of this thesis is to create indicators of socioclimatic vulnerability for small municipalities, using as a base a rural community in the Cariri region, in the state of Paraíba, which is being developed from the adaptation of an existing index, thus creating a new way of calculating this fragility associated with the context of the locality and the social group studied, so that an estimate is obtained as close to the reality as possible by the climate change process. For this, we present qualitative research of bibliographic approach and case study. In order to systematize content and give a better understanding, this thesis is organized into three parts that initially compose the scope of the research and its theoretical basis that, in addition to conceptualizing and oporoting the importance of the indicators listed. Next, we approach the characterization of traditional communities as agents vulnerable to climate change and, finally, the third chapter presents a proposal aimed at small towns, since it has the hypothesis that it is based on the fact that the small rural populations of the state of Paraíba are high-risk groups that present high socioclimatic vulnerability, to the detriment of the strong relationship/dependence with natural resources and agricultural activities. From this, we conclude that the identification of a system of indicators and its subsequent use in the adaptation of an index that calculates climate vulnerability in small rural communities directly contributes to the evolution of research on climate change and its impacts, directly contributing to the process of adaptation, development and governance of localities affected by climate extremes.